Perspectives on the Use of Artificial Intelligence in the Design of Digital Interfaces for Complex Systems - Santos, Eduardo Ferro dos; Rosa, José Guilherme Santa; Mazzoni, Cláudia Ferreira (DAT Journal, 2025)
Artificial Intelligence (AI) has driven significant transformations in the field of Human-Computer Interaction (HCI), particularly in the design of digital interfaces for complex systems. This article investigates how AI has been applied to make interfaces more adaptive, intelligent, and responsive to dynamic and unpredictable usage contexts. An integrative literature review was adopted as the methodological approach, focusing on studies that describe practical applications, advantages, and limitations of AI in interaction design. The findings highlight a growing range of solutions based on recommended systems, conversational agents, assisted design tools, and adaptive interfaces. It is concluded that, while promising, the integration of AI into interface design requires interdisciplinary and ethical approaches that align computational capabilities with the core principles of HCI.